Urban planning and its discontents - Mahadevia, darshini; Sharma, rutool (London Routledge, 2024)
This book, the first of its kind, introduces various aspects of urban planning in India and contributes towards debates on changes required in the current practice. Urban planning in India means many things to city residents and is used generically to include all interventions in the cities, such as public policy design, institutional design, spatial and territorial plans, infrastructure plans, public administration, community participation, and their implementation through programmed, schemes, and projects.
Keywords: City planning Social aspects India; City planning India; Urbanization India